Minimal change in children's lifestyle behaviours and adiposity following a home-based obesity intervention: results from a pilot study. (December 2016) - Spurrier, Nicola; Bell, Lucinda; Wilson, Annabelle; Lowe, Elizabeth; Golley, Rebecca; Magarey, Anthea
Abstract Background/Methods Families of overweight and obese children require support to make sustainable lifestyle changes to improve their child's diet and activity behaviours and in turn weight status. The aim of this pre-post intervention pilot study was to evaluate the feasibility of an individualised home-based intervention for treatment seeking overweight/obese 4–12 year olds and their caregivers. Baseline measures were used to develop a family-specific intervention to improve the quality of the home environment. The intervention was delivered as individualised written recommendations and resources plus phone call and home visit support. Baseline measures were repeated approximately 6 months later. Results Complete data for 24 children was available. Parents reported that 43 % of intervention recommendations were implemented 'very much'. Some descriptive changes were observed in the home environment, most commonly including fruit and vegetables in their child's lunchbox, not providing food treats, and restricting children's access to chips/savoury snack biscuits. At the group level, minimal change was detected in children's diet and activity behaviours or weight status (all p > 0.05). Conclusion The study findings did not support intervention feasibility in its current form. Future interventions should target the family food and activity environment, but also utilise an approach to address the complex social circumstances which limit parent's ability to prioritise healthy family lifestyle behaviours. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR) 3/12/2014.http://www.ANZCTR.org.au . ACTRN12614001264673